2005
DOI: 10.3732/ajb.92.12.2031
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation and relationships among Ulex (Fabaceae) species in southern Spain and northern Morocco assessed by chloroplast microsatellite (cpSSR) markers

Abstract: Genetic variation in 27 populations of Ulex species from southern Spain and northern Morocco (Betic-Rif arc) was assessed using 11 chloroplast microsatellite (cpSSR) markers, which revealed 47 different haplotypes. These nonrecombinant, haploid markers allow measurement of genetic variation in closely related species of Ulex where molecular phylogenetic analyses have not provided a clear view of interspecific relationships. Discriminant analysis indicates that the haplotypes are useful to differentiate among s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 40 publications
1
17
2
1
Order By: Relevance
“…Using universal chloroplast primers referred to as AS, CD and DT (Demesure et al 1995) for PCR and then digestion of amplification products, Pilepic (2002) revealed considerable degree of interspecific polymorphism between Hypericum perforatum and H. maculatum. In 2004, interspecific differences in the genus Citrullus were resolved by Dane et al Genetic variation and relationships among Ulex (Fabaceae) species in Southern Spain and Northern Morocco were similarly assessed by cpSSR markers (Cubas et al 2005). Using three universal primer pairs, Bouhadida (2007) analyzed cpDNA diversity and revealed genetic relationships in the genus Prunus.…”
Section: Mode Of Inheritancementioning
confidence: 99%
“…Using universal chloroplast primers referred to as AS, CD and DT (Demesure et al 1995) for PCR and then digestion of amplification products, Pilepic (2002) revealed considerable degree of interspecific polymorphism between Hypericum perforatum and H. maculatum. In 2004, interspecific differences in the genus Citrullus were resolved by Dane et al Genetic variation and relationships among Ulex (Fabaceae) species in Southern Spain and Northern Morocco were similarly assessed by cpSSR markers (Cubas et al 2005). Using three universal primer pairs, Bouhadida (2007) analyzed cpDNA diversity and revealed genetic relationships in the genus Prunus.…”
Section: Mode Of Inheritancementioning
confidence: 99%
“…One of the reasons is that gorse is an allohexaploid species (2n ¼ 6x ¼ 96 chromosomes; Misset and Gourret, 1996), which complicates studies of its nuclear diversity (Clark and Jasieniuk, 2011). Also, very low cytoplasmic diversity has been found in the Ulex genus (Cubas et al, 2005;Kader Ainouche, personal communication). However, it has been shown that the phenotypic diversity is great, both in the native range and in the invaded regions (Hill et al, 1991;Tarayre et al, 2007;Hornoy et al, 2011), and that it has a genetic basis (Atlan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It is a young genus (four or five million years old) within which little cytoplasmic variation has yet been found (Cubas et al, 2005;Kader Ainouche, personal communication). The Iberian peninsula (Spain and Portugal) is regarded as the centre of diversification of the Ulex genus, because it hosts a dozen Ulex species, with various ploidy levels (Feoli-Chiapella and Cristofolini, 1981).…”
Section: Study Speciesmentioning
confidence: 99%
“…This is more difficult for many nuclear SSRs, where the high heterozygosity and long size make distinct sequences difficult to obtain (Siragusa and Carimi, 2009). Therefore, they would be useful markers to gain more insights in genetic relationship studies of closely related species and populations, phylogeographic studies within a species, and marker-assisted selection (Provan et al, 2001;Cubas et al, 2005;Chen et al, 2007;Siragusa and Carimi, 2009;Melotto-Passarin et al, 2011).…”
Section: Introductionmentioning
confidence: 99%